Responses of peatland vegetation to 15‐year water level drawdown as mediated by fertility level. (26th September 2019) - Kokkonen, Nicola A. K.; Laine, Anna Maria; Laine, Jukka; Vasander, Harri; Kurki, Kirsi; Gong, Jinnan; Tuittila, Eeva‐Stiina
Abstract: Questions: Peatland ecosystems are a globally important carbon storage that is predicted to turn into a carbon source due to water level drawdown (WLD) associated with climate change. The predictions assume stable plant communities but how realistic is this assumption? If the vegetation is not stable, what are the nature and rate of changes? Location: Peatland complex in Southern Finland. Methods: We conducted a water level drawdown (WLD of 10 cm) experiment over 17 years in three peatland types differing in their fertility. On each peatland type, we included an adjacent forestry drained (FD, with water table ca. 40 cm lower than in control) area for comparison. Results: Peatland type had a clear impact on the response to WLD: at the ecosystem level, the two minerotrophic fens underwent rapid species turnover, while the vegetation in nutrient‐poor bog was more resilient to change. In nutrient‐rich sites, WLD initiated tree canopy development and created understorey conditions that strengthened impact of WLD. In nutrient‐poor site, tree establishment was seen only in the FD area. In addition to high nutrient level, high wetness accelerated change at the plant community level, where we found three types of responses: accelerating change, decelerating change, and stability. Succession resulted in an overall loss of community heterogeneity. Conclusions: Interaction between hydrology, nutrient availability, and biological factors in boreal peatlands is important: the drop in water table required to achieve the shift from open peatland to forested system is inversely proportional to the nutrient level of the system. The results suggest that predictive models of peatland functions under climate change should consider compositional change for fens and their diverse plant communities but are more realistic for bogs. The response of bog vegetation to climate change may, however, be more dependent on changes in rainfall regime and therefore needs to be further addressed. Abstract : Our paper tracks for the first time the different development pathways of varying peatland vegetation types in response to long‐term water level drawdown. We found that the so‐called tipping point, a drop of water table at which an open peatland undergoes significant vegetation change or transitions to a forest system, is inversely proportional to the nutrient level of the system.